Iskustvo : Recent Soviet Paintings - Wardell, Michael (Richmond, Victoria : 13 Verity Street, 1990)
Bandzeladze, Alexander M. ; Adjiashvily, Semyon ; Edzgveradze, Gia ; Zautashvili, Gela G. ; Vassilkov, Gennadi A. ; Lindin, Evgeni S. ; Birstein, Anna M. ; Filatov, Nikolai V. ; Zvezdochetov, Konstantin V. ; Filippov, Andrei S. ; Mironenko, Sergei I. ; Zvezdochetova, Larisa J. ; Fishkin, Vadim V. ; Fomsky, Pavel P. ; Alekseev, Nikita F. ; Turnova, Natalia P.
Iskustvo : Recent Soviet Paintings, 13 Verity Street, Richmond and Linden, St. Kilda, March 21 - Arpil 15 1990 ; Geelong Regional Art Gallery, April 20 - June 7 1990 ; Latrobe Valley Arts Centre, July 6 - Aug. 2 1990 ; Castlemaine Regional Arts Centre, Aug. 10 - Sept. 2 1990 ; College Gallery SACE, Adelaide, Sept. 8 - Oct. 13 1990 ; McClelland Art Gallery, Frankston, Oct. 21 - Dec. 2 1990
boek
Keywords: Rusland